Case Report: Innovative anesthetic approaches for whole lung lavage in an infant with pulmonary alveolar proteinosis - Chen, Jiaxiang; Shi, Xiaoli; Tu, Youbing; Chen, Yuanzhen; Wang, Xueqing; Shen, Jing; Xu, Liang; Meng, Ligang (Frontiers in Pediatrics, 2025)
IntroductionPulmonary alveolar proteinosis (PAP) is a rare disease in infancy characterized by the accumulation of lipoprotein material within the alveoli, leading to impaired gas exchange, ventilation-perfusion mismatch, and, in severe cases, respiratory failure that may result in death. Treatment options include medical therapy and whole lung lavage (WLL), typically requiring lung isolation techniques or extracorporeal membrane oxygenation. Previous studies have reported the application of several lung isolation techniques in pediatric WLL. However, the use of a bronchial blocker (BB) in infant WLL has not been previously reported.Case descriptionThis study reports the anesthesia management of a 12-month-old infant diagnosed with secondary PAP, complicated by severe pneumonia and patent ductus arteriosus. The child presented with respiratory failure requiring WLL. The anesthesia method employed was intravenous general anesthesia, and airway management involved using a BB placed outside the endotracheal tube to facilitate one-lung ventilation (OLV). The procedure successfully maintained blood oxygen levels above 90%, and the WLL was completed without any anesthetic complications.ConclusionThis case demonstrates that using endotracheal intubation combined with extraluminal placement of a BB for lung isolation is a viable and effective approach for performing WLL in infants.